1996
DOI: 10.1029/95wr03245
|View full text |Cite
|
Sign up to set email alerts
|

An Effect of Seiche on Groundwater Seepage Rate into Lake Biwa, Japan

Abstract: Numerical analyses of seiche and continuous measurements of water level and groundwater seepage rates into Lake Biwa, Japan, were made to evaluate interactions between surface and subsurface waters. An automatic seepage meter was used to obtain continuous groundwater seepage rates. Analyses of the fluctuations of seepage rate and water level in the lake were done using the fast Fourier transform method. The finite element method was used for analysis of the seiche in the lake. Dominant periods of fluctuations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…4a). Taniguchi and Fukuo (1996) found an effect of seiches on groundwater discharge into Lake Biwa, Japan. They found that the dominant periods of fluctuations of the groundwater seepage rate observed in Lake Biwa agreed well with those of the fluctuations of the water levels in the lake, which were calculated numerically by a finite element method.…”
Section: Periodic Changes In Sgdmentioning
confidence: 97%
“…4a). Taniguchi and Fukuo (1996) found an effect of seiches on groundwater discharge into Lake Biwa, Japan. They found that the dominant periods of fluctuations of the groundwater seepage rate observed in Lake Biwa agreed well with those of the fluctuations of the water levels in the lake, which were calculated numerically by a finite element method.…”
Section: Periodic Changes In Sgdmentioning
confidence: 97%
“…Quantitative estimation of fluxes of recharging or discharging water provides fundamental information. To date, fluid fluxes were estimated in various environments, such as lakes [e.g., Shaw et al , 1990; Taniguchi and Fukuo , 1996], coastal zones [e.g., Cable et al , 1996; Moore , 1996; Spinelli et al , 2002; Taniguchi et al , 2002], submarine hydrothermal areas [e.g., Schultz et al , 1992, 1996; Cooper et al , 2000], and accretionary prisms in subduction zones [e.g., Carson et al , 1990; Tryon et al , 2001], with seepage meters, diffuse flowmeters, piezometers, and by chemical tracer methods.…”
Section: Introductionmentioning
confidence: 99%
“…Seepage meters were developed originally by engineers studying leakage of canal bank linings (Israelson and Reeve 1944) but were largely ignored by the scientific research community until the 1970s when Lee (1977) demonstrated their effectiveness in evaluating groundwater seepage along shorelines. Since then, different forms of the seepage meter have been used with varying degrees of success in many freshwater and marine environments (e.g., Bokuniewicz 1980Bokuniewicz , 1992Prepas 1989, 1990;Belanger and Montgomery 1992;Reay et al 1992;Libelo and MacIntyre 1994;Cable et al 1996;Gallagher et al 1996;Taniguchi and Fukuo 1996;Cable et al 1997a,b;Corbett et al 2000;Chanton et al 2003;Cable et al 2004). The simplicity of seepage meter design and deployment makes the device simultaneously attractive for field work and the bane of the researcher.…”
Section: Introductionmentioning
confidence: 99%